HAZARDOUS NATURAL PHENOMENA: EARTHQUAKES AND MUDFLOWS - Vasliddinova Muslima, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, examines two of the most dangerous natural hazards — earthquakes and mudflows (sel). The author explains how these phenomena occur, what damage they  cause,  and  what  safety  measures  must  be  followed  to  protect  human  life  and property. The article emphasises that awareness and correct behaviour during natural disasters can save lives.